(C)overt linguistic racism: Eastern-European background immigrant women in the Australian workplace - Tankosic, Ana; Dovchin, Sender (SAGE PUBLICATIONS LTD, 2021)
Linguistic racism explores the varied ideologies that may generate and endorse monolingual, native, and normative language practices, while reinforcing the discrimination and injustice directed towards language users whose language and communicative repertoires are not necessarily perceived as standard and normal. This article, thus, investigates linguistic racism, as a form of existing, but newly defined, racism against unconventional ethnic language practices experienced by Eastern-European immigrant women in the Australian workplace. Our ethnographic study shows that, once these women directly or subtly exhibit their non-nativism, through a limited encounter with local expressions, non-native language skills, and ethnic accents, they become victims of covert and overt linguistic racism in the form of social exclusion, mockery, mimicking, and malicious sarcasm in the hierarchical power environment of the workplace. As a result, these migrants can suffer from long-lasting psychological trauma and distress, emotional hurdles, loss of credibility, and language-based inferiority complexes. We, as researchers, need to highlight the importance of combatting workplace linguistic racism and revealing language realities of underprivileged communities. In that way, we can assist them in adapting to host societies and help them regain some degree of power equality in their institutional environments.